Extracorporeal Membrane Oxygenation for COVID-19: Case Report of Nine Patients - Hua, Jing; Zhang, Xin; Wang, Na; Ran, Linyu; Wang, Shengyun; Huang, Chiungwei; Gao, Wei; Qian, Chenchen; Guo, Wei; Liu, Zhongmin; Li, Qiang; Wang, Feilong (Frontiers in Medicine, 2021)
Acute respiratory distress syndrome (ARDS) was the fatal comorbidity of critically ill patients with COVID-19, which often end up with respiratory supports. However, the safety and effectiveness of Extracorporeal Membrane Oxygenation (ECMO) in the treatment of COVID-19 remains to be elucidated at present. Here we reported nine patients who received ECMO duo to severe SARS-CoV-2 infection in Wuhan, China. Our initial experiences suggested that careful selecting patients as well as managing by a well-trained team were critical to implement ECMO in patients with COVID-19. More randomized controlled trials with larger sample sizes are needed to evaluate the usefulness of ECMO in patients with COVID-19.